Agricultural extension services: From transfer of technology to facilitation for innovation - Davis, Kristin E.; Gandhi, Rikin; Koo, Jawoo; Kramer, Berber; Miller, Alesha; Repishti, Jona; Spielman, David J.; Sulaiman V., Rasheed (International Food Policy Research Institute, 2025)
Agricultural extension and rural advisory services play a key role in the agrifood systems of many low- and middle-income countries by supporting farmers’ efforts to enhance productivity, strengthen resilience to shocks, and conserve the natural resource base on which these systems depend. This chapter applies IFPRI’s “best fit” conceptual framework to examine the global evolution of agricultural extension and rural advisory services over the past 50 years, as well as the shift from a “transfer of technology” approach to a more sophisticated “facilitation for innovation” paradigm.